a+(1)/(2)b+(2)/(5)+(3)/(2)a+(1)/(4)b

3 answers

To simplify the expression, we can combine like terms:
First, let's add the terms that have "a":
a + (3/2)a = (2/2)a + (3/2)a = (5/2)a
Now, let's add the terms that have "b":
(1/2)b + (1/4)b = (2/4)b + (1/4)b = (3/4)b
Finally, we can put it all together:
a + (1/2)b + (2/5) + (3/2)a + (1/4)b = (5/2)a + (3/4)b + (2/5)
a+1/2b+2/5+3/2a+1/4b
To simplify the expression, we can combine like terms:
First, let's combine the terms that have "a":
a + 3/2a = (2/2)a + (3/2)a = (5/2)a
Next, let's combine the terms that have "b":
1/2b + 1/4b = (2/4)b + (1/4)b = (3/4)b
Now, let's put it all together:
a + 1/2b + 2/5 + 3/2a + 1/4b = (5/2)a + (3/4)b + 2/5